Sjogren-Larsson syndrome brain volumetric reductions demonstrated with an automated software - Castro, José Thiago de Souza de; Saab, Camilo Lotfi; Souto, Mariam Patrícia Auada; Ortolam, Juliane Giselle; Steiner, Carlos Eduardo; Rezende, Thiago Junqueira Ribeiro de; Reis, Fabiano (Arquivos de Neuro-Psiquiatria, 2023)
Background Sjogren-Larsson syndrome (SLS) is a neurocutaneous disease with an autosomal recessive inheritance, caused by mutations in the gene that encodes fatty aldehyde dehydrogenase (ALDH3A2), clinically characterized by ichthyosis, spastic diplegia, and cognitive impairment. Brain imaging plays an essential role in the diagnosis, demonstrating a nonspecific leukoencephalopathy. Data regarding brain atrophy and grey matter involvement is scarce and discordant.Objective We performed a volumetric analysis of the brain of two siblings with SLS with the aim of detecting deep grey matter nuclei, cerebellar grey matter, and brainstem volume reduction in these patients.Methods Volume data obtained from the brain magnetic resonance imaging (MRI) of the two patients using an automated segmentation software (Freesurfer) was compared with the volumes of a healthy control group.Results Statistically significant volume reduction was found in the cerebellum cortex, the brainstem, the thalamus, and the pallidum nuclei.Conclusion Volume reduction in grey matter leads to the hypothesis that SLS is not a pure leukoencephalopathy. Grey matter structures affected in the present study suggest a dysfunction more prominent in the thalamic motor pathways.
Keywords: Sjogren-Larsson Syndrome; Neurocutaneous Syndromes; Thalamic Diseases; Brain Diseases